MOLECULAR CHARACTERIZATION OF DYE DEGRADING Aspergillus flavus STRAIN GKRS09 AND FT-IR ANALYSIS OF THE DEGRADED PRODUCTS (Journal of Pharmaceutical Negative Results, 2023)
Azo dyes have aromatic rings, sulfonic groups, and azo bonds (-N=N-) making it one of the most often used dye classes in industry and a substantial class of environmental pollutants. The majority of textile dyes are flushed away through drainage systems. Due to their persistent nature and toxicity to both humans and animals, these dyes must be removed from the environment. The current work focuses on the biodegradation of such azo dye, Malachite Green (MG) and Congo Red (CR), by potent dye degrading fungal strain FSS4 isolated from textile water in Dravyavati river, Rajasthan, India. Potato dextrose broth with 100 mg/l MG and CR was used for dye degradation assay. FTIR (PerkinElmer Spectrum TwoTM IR spectrometer) examined the degradation products from 4000–400 cm–1 wavenumber range. Molecular characterization identified this potent fungus as Aspergillus flavus strain GKRS09 (GenBank accession number; OK236565). The strain demonstrated remarkable decolorization and degradation properties after 07 days. FT-IR study showed that A. flavus strain GKRS09 decomposed Malachite Green and Congo Red dyes into non-toxic products. The isolate GKRS09 can treat azo dye-containing industrial effluent economically and sustainably.